2019
DOI: 10.1186/s12885-018-5252-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mean platelet volume predicts poor prognosis in metastatic colorectal cancer patients treated with first-line chemotherapy: results from mCRC biomarker study

Abstract: BackgroundMetastatic colorectal cancer (mCRC) is a major cause of death of malignant tumor and the valuable prognostic biomarker for chemotherapy is crucial in decreasing mortality. Previous studies have proved the prognostic value of the mean platelet volume (MPV) in survival of primary operable CRC patients. However, the prognostic impact of MPV in mCRC is still unclear. In this study, we aimed to clarify the prognostic role of MPV in mCRC undergoing standard first-line chemotherapy.MethodsFrom January 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“… 3 The complicated interactions between activated platelets and cancer cells lead to tumour growth, aberrant angiogenesis, invasion and metastasis. 4–6 A mounting body of evidence suggests that MPV plays an important prognostic role in various types of tumours, including upper gastrointestinal tumours, 7–14 colorectal cancer, 15 16 lung cancer, 17–19 breast cancer 20–22 and urothelial carcinoma. 23 24 However, the association between MPV level and cancer prognosis has not been comprehensively investigated due to the inevitable heterogeneity of the samples in different studies.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The complicated interactions between activated platelets and cancer cells lead to tumour growth, aberrant angiogenesis, invasion and metastasis. 4–6 A mounting body of evidence suggests that MPV plays an important prognostic role in various types of tumours, including upper gastrointestinal tumours, 7–14 colorectal cancer, 15 16 lung cancer, 17–19 breast cancer 20–22 and urothelial carcinoma. 23 24 However, the association between MPV level and cancer prognosis has not been comprehensively investigated due to the inevitable heterogeneity of the samples in different studies.…”
Section: Introductionmentioning
confidence: 99%
“…There were no measured differences in mean cell volume (MCV) or mean platelet volume (MPV) values in Dox treated mice at any point in time. These parameters were recently reported to play a significant role in some cases of chemotherapy response [23][24][25][26]. We therefore tested these clinical parameters to potentially reveal their role in systemic hematopoietic effects.…”
Section: Resultsmentioning
confidence: 99%
“…Some evidence suggests the association between increased MPV and poor overall survival in patients undergoing surgical treatment [ 39 ]. On the other hand, decreased pretreatment MPV was showed to predict worse prognosis in the population with advanced CRC qualified to first-line palliative chemotherapy [ 16 ]. In the present study, we observed no differences in MPV in CRC patients through TNM stages I-IV which is in agreement with previously published data [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential prognostic role of the combinations of the SIR parameters (such as lymphocytes, neutrophils, and platelets obtained by the peripheral blood test), including the platelet-to-lymphocyte ratio (PLR), neutrophil platelet score (NPS), or mean platelet volume (MPV) to platelet count (PC) ratio, was investigated in various cancers, including CRC [ 8 10 ]. However, majority of the studies focused on the primary operable cancer [ 11 15 ]; some of them observed patients with advanced diseases [ 16 18 ] or patients in all clinical stages [ 19 ]. The relation between platelet indices and clinical features is still inconsistent.…”
Section: Introductionmentioning
confidence: 99%